2011
DOI: 10.1182/blood-2011-05-354233
|View full text |Cite
|
Sign up to set email alerts
|

No difference in outcome between children and adolescents transplanted for acute lymphoblastic leukemia in second remission

Abstract: Acute lymphoblastic leukemia (ALL) in second complete remission is one of the most common indications for allogeneic hematopoietic stem cell transplantation (HSCT) in pediatric patients. We compared the outcome after HCST of adolescents, aged 14 to 18 years, with that of children (ie, patients < 14 years of age). Enrolled in the study were 395 patients given the allograft between January 1990 and December 2007; both children (334) and adolescents (61) were transplanted in the same pediatric institutions. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 34 publications
5
31
0
Order By: Relevance
“…10,25,26 The outcome of children transplanted from UDs acquires particular value in light of the fact that this type of allograft was employed in patients either with poor-prognosis molecular lesions, such as FLT3-ITD, or in infants, or in children with M7-AML or complex karyotype or in those patients not responding to the first course of induction therapy, these subgroups notoriously predicting a grim prognosis. 2,8,17,27,28 We and others have previously provided evidence that the outcome of children with acute lymphoblastic leukemia given HSCT from an UD has improved over time, 12,13,26 and the present results confirm that currently, thanks to the improvements in HLA typing obtained through the use of high-resolution molecular techniques and the optimization of GVHD prevention and treatment, post-transplantation outcome is not influenced by the type of donor used, either related or unrelated.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…10,25,26 The outcome of children transplanted from UDs acquires particular value in light of the fact that this type of allograft was employed in patients either with poor-prognosis molecular lesions, such as FLT3-ITD, or in infants, or in children with M7-AML or complex karyotype or in those patients not responding to the first course of induction therapy, these subgroups notoriously predicting a grim prognosis. 2,8,17,27,28 We and others have previously provided evidence that the outcome of children with acute lymphoblastic leukemia given HSCT from an UD has improved over time, 12,13,26 and the present results confirm that currently, thanks to the improvements in HLA typing obtained through the use of high-resolution molecular techniques and the optimization of GVHD prevention and treatment, post-transplantation outcome is not influenced by the type of donor used, either related or unrelated.…”
Section: Discussionsupporting
confidence: 75%
“…[9][10][11] The use of high-resolution molecular typing techniques for selecting an unrelated donor (UD) has also dramatically reduced the risk of immune-mediated complications and TRM, thus widening the indications for HSCT from an unrelated volunteer, which now are in part coincident with those for matched-related HSCT. 12,13 Although largely used in the past, 14,15 more recently the role of autologous (AUTO) HSCT has been questioned, especially in view of similar efficacy to repeated courses of intensive high-dose cytarabine (HD-AraC)-based consolidation chemotherapy for prevention of disease recurrence. 5,16 We recently reported that risk-oriented treatment and broad use of HSCT in children with CR1 AML resulted in a long-term outcome, which compares favorably with that reported in other patient series.…”
Section: Introductionmentioning
confidence: 99%
“…DFS usually reported in children transplanted for high-risk leukemia from sibling or unrelated donors vary between 50 and 70%. 25,[27][28][29][30][31][32][33]40 Weiss et al 37 report a similar DFS (84%) using CsA alone as GVHD prophylaxis but in patients transplanted only from MSDs. 37 They also used CsA while targeting a lower and narrower TBC range (80-130 ng/mL) compared with those usually recommended (100-200 ng/mL).…”
Section: Discussionmentioning
confidence: 84%
“…This confirms the major role of antithymocyte globulin as part of GvHD prophylaxis in patients transplanted from unrelated donors. 11 We also report a low rate of TRM compared with other series where average TRM reaches 20-25%, 25,29,30,34 even though a large variability (7-45%) is possible. 27,35,38,39 Our results suggest that close monitoring of CsA therapy may permit a substantial reduction of GvHD-related mortality.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation